The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1681/asn.2020101531
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biomarkers of Iron Stores Are Associated with Increased Risk of All-Cause Mortality and Cardiovascular Events in Nondialysis CKD Patients, with or without Anemia

Abstract: BackgroundApproximately 30%–45% of patients with nondialysis CKD have iron deficiency. Iron therapy in CKD has focused primarily on supporting erythropoiesis. In patients with or without anemia, there has not been a comprehensive approach to estimating the association between serum biomarkers of iron stores, and mortality and cardiovascular event risks.MethodsThe study included 5145 patients from Brazil, France, the United States, and Germany enrolled in the Chronic Kidney Disease Outcomes and Practice Pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 36 publications
1
35
0
3
Order By: Relevance
“…In these PD patients, median ferritin levels did not exceed 300 ng/mL (262.1 ng/mL) and the hemoglobin level was well maintained within the target range recommended in the JSDT guidelines [17]. The importance of treating anemia and iron deficiency in CKD patients has recently been receiving increasing attention, as several studies have demonstrated that these conditions are associated with an increased risk of hospitalizations, cardiovascular events, or all-cause mortality [18,19]. FC is expected to contribute to the treatment of anemia and iron deficiency in CKD patients, but caution regarding iron overload is required, especially in PD patients.…”
Section: Discussionmentioning
confidence: 88%
“…In these PD patients, median ferritin levels did not exceed 300 ng/mL (262.1 ng/mL) and the hemoglobin level was well maintained within the target range recommended in the JSDT guidelines [17]. The importance of treating anemia and iron deficiency in CKD patients has recently been receiving increasing attention, as several studies have demonstrated that these conditions are associated with an increased risk of hospitalizations, cardiovascular events, or all-cause mortality [18,19]. FC is expected to contribute to the treatment of anemia and iron deficiency in CKD patients, but caution regarding iron overload is required, especially in PD patients.…”
Section: Discussionmentioning
confidence: 88%
“…It is interesting the association between TSAT ≥ 20% and the lower risk of death seen in the present study. Such association was found and well explored in a recent CKDopps study with pre-dialysis chronic kidney disease (CKD) patients [ 15 ]. However, whether low TSAT was just a marker of inflammation/malnutrition [ 16 , 17 ] or iron replacement would be effective to improve outcomes is a question that could only be answered through interventional studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent international (Brazil, France, Germany, and United States) observational study included 1545 nondialyzed CKD patients with and without anemia [27]. Patients with TSAT ≤15% had the highest risks of all‐cause mortality and major adverse cardiovascular events, compared with patients with TSAT 26%–35%.…”
Section: Id Is a Factor Of Poor Prognosismentioning
confidence: 99%